2021
DOI: 10.1002/ece3.8124
|View full text |Cite
|
Sign up to set email alerts
|

Does the intensive grazing and aridity change the relations between the dominant shrub Artemisia kopetdaghensis and plants under its canopies?

Abstract: The interspecific plant interactions along grazing and aridity stress gradients represent a major research issue in plant ecology. However, the combined effects of these two factors on plant-plant interactions have been poorly studied in the northeast of Iran. To fill this knowledge gap, 144 plots were established in 12 study sites with different grazing intensities (high vs. low) and climatic characteristics (arid vs. semiarid) in northeastern Iran. A dominant shrub, Artemisia kopetdaghensis, was selected as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…This result was consistent with the significant effects of Artemisia on plant biodiversity structure, especially on taxonomic diversity (Bahalkeh et al, 2021;Rahmanian et al, 2021)…”
Section: Plant Biodiversity Through the Presence Of Nurse Plants And ...supporting
confidence: 87%
See 2 more Smart Citations
“…This result was consistent with the significant effects of Artemisia on plant biodiversity structure, especially on taxonomic diversity (Bahalkeh et al, 2021;Rahmanian et al, 2021)…”
Section: Plant Biodiversity Through the Presence Of Nurse Plants And ...supporting
confidence: 87%
“…It seems that an increased taxonomic diversity in Artemisia patches and functional and phylogenetic diversity in Stipa patches are influenced by the presence of a wide range of plant species or by some specific plant species with different functional identities and distant evolutionary relatedness. However, some recent studies have shown negative or neutral effects of Artemisia patches on plant biodiversity structure, especially on taxonomic diversity (Bahalkeh et al, 2021 ; Rahmanian et al, 2021 ). These contrasting results are likely to be contingent on different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted on plant-plant interactions in Artemisia steppes from arid northeast Iran observed a neutral community-level response with contrasting species-level responses in low grazing conditions (Bahalkeh et al, 2021). By contrast, using only a communitylevel approach, Rahmanian et al (2021) found competition in low grazing conditions and facilitation in high grazing conditions in a semi-arid climate. However, there are no studies that assessed plant-plant interactions along a grazing gradient at both the community and species-group levels in Artemisia steppes.…”
Section: Introductionmentioning
confidence: 84%
“…Functional diversity was assessed based on 10 qualitative and quantitative traits that were considered as important functional traits of plant taxa in severe environments, and associated with the presence of nurse species (Perez‐Harguindeguy et al, 2013; Rahmanian et al, 2021). These functional traits were plant height, seed mass, leaf area (LA), specific leaf area (SLA), leaf dry matter content (LDMC), life form, life span, clonality, thorniness and palatability (Rafiee et al, 2022).…”
Section: Methodsmentioning
confidence: 99%